Effect of dietary supplementation with flavonoid from Scutellaria baicalensis Georgi on growth performance, meat quality and antioxidative ability of broilers - Xiu-dong LIAO; Qian WEN; Ling-yan ZHANG; Lin LU; Li-yang ZHANG; Xu-gang LUO (Journal of Integrative Agriculture, 2018)
An experiment was conducted to investigate the effect of dietary supplementation with flavonoid from Scutellaria baicalensis Georgi (SBGFN) as SBGFN-zinc (SBGFN-Zn) on growth performance, meat quality, immune responses and antioxidation of broilers. A total of 450 one-d-old Arbor Acres male broilers were randomly allocated to 5 treatments with 6 replicates of 15 birds per replicate for each treatment in a completely randomized design. Birds were fed a SBGFN-unsupplemented corn-soybean meal basal diet (control) or the basal diet supplemented with 60, 120, 180 or 240 mg SBGFN kg−1 from SBGFN-Zn for 42 d. Dietary SBGFN supplementation affected (P<0.03) drip loss in thigh muscle, total superoxide dismutase (T-SOD) and glutathione peroxidase (GSH-Px) activity in liver of broilers at 42 d of age. Chicks fed the diets supplemented with 120, 180 and 240 mg SBGFN kg−1 had lower (P<0.03) drip loss of thigh muscle than those fed the control diet. Chicks fed the diet supplemented with 180 mg SBGFN kg−1 had higher (P<0.03) liver T-SOD and GSH-Px activity than those fed the diets supplemented with 0, 60 and 120 mg SBGFN kg−1. The results from the present study indicate that dietary supplementation with 180 mg SBGFN kg−1 as SBGFN-Zn improved both meat quality and antioxidative ability of broilers.